2014
DOI: 10.1186/s13028-014-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Bit-related lesions in Icelandic competition horses

Abstract: BackgroundOral lesions related to the use of the bit and bridle are reported to be common findings in horses worldwide and represent an important animal welfare issue. In order to provide an overview of bit-related lesions in Icelandic competition horses, a field examination of the rostral part of the oral cavity was performed in 424 competition horses coming to the two major national horse events in Iceland in 2012. Records from repeated examination of 77 horses prior to the finals were used to assess potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 8 publications
3
58
2
Order By: Relevance
“…presence was strongly associated with using a snaffle bit [5]. In contrast, using a ported curb bit was more likely to be associated with lesions on the bars of the mouth.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…presence was strongly associated with using a snaffle bit [5]. In contrast, using a ported curb bit was more likely to be associated with lesions on the bars of the mouth.…”
Section: Discussionmentioning
confidence: 86%
“…Prior to the start of a multi‐day competition, 43% of Icelandic horses had oral ulcers, most of which were mild and located around the commissures of the lips. When re‐evaluated prior to the final round of competition, the prevalence of ulcers at the lip commissures had not changed, and their presence was strongly associated with using a snaffle bit . In contrast, using a ported curb bit was more likely to be associated with lesions on the bars of the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent increase in scientific studies assessing the impact of training, tack use and competition on equine welfare. For example, studies have shown significant lesions in the mouths of Finnish trotters and Icelandic horses when used in competition from the action of the bit [7,32]. The use of coercive hyperflexion of the head and neck or Rollkur, for example in dressage horses, has been shown to cause adverse behavioural [15] and physiological indicators [33], suggesting increased stress in these animals compared to working in a less flexed position.…”
Section: Impact Of Inappropriate Training or Use Of Horsesmentioning
confidence: 99%
“…The formation of bone spurs in affected horses is apparently due to inflammation associated with repeated incidents of bit-induced bruising, laceration, and/or ulceration of the interdental gums [7,[121][122][123]. Such gum lesions reportedly occurred in 26% of 261 Trotters observed after a race [124], increased from 8% before to 31% after events in 77 competition horses [125], and were more common and severe in racehorses than polo ponies [120]. All such lesions are painful [107], and human experience would suggest that the intensity of that pain would be increased when there is further direct compressive contact between these lesions and a bit.…”
Section: The Interdental Spacementioning
confidence: 99%
“…Nevertheless, several observations suggest that the tongue may be somewhat protected from bit-induced penetrative injuries. Studies that reveal significant bit-related injuries at multiple oral sites report no or very low occurrences of significant tongue lacerations or ulcers [120,124,125,129,130]. The tough keratinized squamous epithelial lining of at least the dorsal surface of the tongue [131] may contribute to this, but it might also make bruises from non-penetrative bit-related compression more difficult to detect.…”
Section: The Tonguementioning
confidence: 99%